Biodegradation of a Mixed Manure–Lignocellulosic System—A Possibility Study - Darja Pečar; Maša Islamčević Razboršek; Andreja Goršek (Applied Sciences, 2021)
Animal waste is generated at an increased rate, and its disposal is attracting wide public attention. Anaerobic digestion is considered the most promising option for reducing this waste, and simultaneously, it produces renewable energy. Lignin contained in lignocellulosic biomass is hardly biodegradable, thus pre-treatment has to be considered prior to digestion. The possibility of biological pre-treatment of chicken manure with sawdust using Pleurotus ostreatus fungi was investigated in our study. This animal waste was used as a substrate for further biogas production. To provide a better nutrient balance, we added two different co-substrates, wheat straw and Miscanthus. Mixtures with different mass ratios of chicken manure with sawdust/ordinary wheat straw, as well as chicken manure with sawdust/pre-treated wheat straw were incubated for 30 d. The same experiments were performed with Miscanthus. During incubation, samples were taken at predetermined time intervals, and the concentration of acid-insoluble lignin was determined. Additionally, concentrations of glucose and xylose in the filtrate taken at the end of the Klasson procedure were determined in the initial samples and in the samples after 30 d of incubation. Despite our expectations, almost no lignin degradation was observed. Insignificant decreases in glucose and xylose concentrations after 30 d is attributed to fungi ingestion. Obtained results show that Pleurotus ostreatus, as a white-rot fungi with a unique enzymatic system and as generally preferred organisms for lignin degradation, is, therefore, not suitable for delignification of this particular animal waste.